Use of Reticulated Hyaluronic Acid Alone or Associated With Ozone Gas in the Treatment of Osteoarthritis Due to Hip Dysplasia in Dogs - Silva Júnior, José I. S.; Rahal, Sheila C.; Santos, Ivan F. C.; Martins, David J. C.; Michelon, Fernanda; Mamprim, Maria J.; Tomacheuski, Rubia M.; Correia, Luiz E. C. S. (Frontiers in Veterinary Science, 2020)
This study aimed to evaluate reticulated hyaluronic acid alone or associated with ozone gas in the treatment of osteoarthritis due to hip dysplasia in dogs. Fourteen client-owned dogs were randomly assigned into two groups: Group 1 - single intra-articular injection of hyaluronic acid; Group 2 - single intra-articular infiltration injection of hyaluronic acid associated with ozone gas. Each hip joint received an average of 0.75 mL of reticulated hyaluronic acid ultrasound-guided. Ozone gas at a dose of 45 µg/mL was incorporated into hyaluronic acid by insufflation. Dogs were evaluated for body condition scoring, orthopedic examination and radiographic scores of the hip joints, lameness scores, goniometric measurements of the hip joints, and kinetic analysis. The evaluations were conducted immediately before treatments (M0), and at days 30 (M1), 60 (M2) and 90 (M3) after treatments. There were no significant differences in body mass and body condition scoring (5-point scale) in each group in all evaluation moments. Orthopedic examination scores showed improvement after treatments, but no change was detected in radiographic scores. No significant differences were found between groups and in each group between moments for goniometric measurements of the hip joints. No statistical differences between groups were found concerning the lameness score. There were significant differences for lameness score among moments in Group 1, being M0>M2 and M0>M3, and Group 2 in which M0>M1, M0>M2 and M0>M3. The percent change of the PFV (%BW) comparing M0 and M1 was positive in eight and negative in six hind limbs in Group 1, and positive in 12 and negative in two hind limbs in Group 2. In conclusion, the intra-articular viscosupplementation alone or associated with ozone gas showed similar effects and allowed statistical improvement of lameness scores, and positive percentage change of PFV (%BW) in 71.43% of the hind limbs.